Terapan konsep feminisme talbiah dalam cerpen Akar Cinta karya Aminah Mokhtar - Abdul Halim Ali (Tanjong Malim, 2019)
Terapan konsep feminisme talbiah dalam cerpen Akar Cinta karya Aminah Mokhtar by Abdul Halim Ali